Antioxidant activity and DNA damage protection of mung beans processed by solid state fermentation with Cordyceps militaris SN-18. (October 2015) - Xiao, Yu; Zhang, Qiuqin; Miao, Junqing; Rui, Xin; Li, Teng; Dong, Mingsheng
Abstract: In this study, solid state fermentation of mung beans by Cordyceps militaris SN-18 ( C. militaris -fermented mung beans, CFMB) was performed. The effects of fermentation on phenolic content, antioxidant activity, and DNA damage protection of mung beans through various polarities solvent extracts were determined. Results showed that phenolic content, antioxidant activities, and DNA damage protection of mung beans were significantly enhanced by fermentation. The water extract of CFMB exhibited the highest phenolic content, DPPH radical scavenging activity, ferric reducing antioxidant power, reducing power, and DNA damage protection. During fermentation, shikimic acid, chlorogenic acid, vanillic acid, rutin, sinapic acid, and luteolin of mung beans were significantly increased. A clear correlation was found between phenolic content and antioxidant activity. Thus, CFMB with enhanced phenolic compounds, antioxidant activity, and DNA damage protection may be effective in the prevention of oxidative damage-induced disease, and it can serve as a novel nutraceutical and functional food in health promotion. Graphical abstract: Highlights: A novel solid state fermentation with Cordyceps militaris was used to produce fermented mung beans. Phenolic content and antioxidant activities of mung beans were enhanced by solid state fermentation. Fermented mung beans showed higher protection effects for damaged DNA. Phenolics were correlated with the antioxidant activities. A solid state fermentation process could obtain a novel nutraceutical and functional food.